The use and maintenance of the automatic cleaning machine in the Central Sterile Supply Department of Traditional Chinese Medicine hospital (中医院消毒供应室全自动清洗消毒机的使用及维护) - MIAO Yanmei (苗艳梅); WANG Jingju (王京菊) (中西医结合护理)
This paper summarized the operation method, routine maintenance and potential problems in using the automatic cleaning machine in the Central Sterile Supply Department of Traditional Chinese Medicine hospital. The automatic cleaning machine has advantages of reliable disinfection effect and easy-to-use operation, and it is of great significance to improve the cleaning and disinfection quality in the Central Sterile Supply Department. It is required to strengthen equipment inspection and maintenance in the daily use of automatic cleaning machine, in order to ensure the safety in supple and use of medical instruments. (本文总结了全自动清洗消毒机的使用方法、日常维护以及使用中可能出现的问题。全自动清洗消毒机的清洗消毒效果可靠, 操作简便安全, 对提高消毒供应室清洗消毒质量有着重要意义。全自动清洗消毒机属于精密仪器, 应加强设备检查和保养, 以保证医疗物品的安全供应与使用。)